The Affinity of the S9.6 Antibody for Double-Stranded RNAs Impacts the Accurate Mapping of R-Loops in Fission Yeast. Issue 3 (2nd February 2018) - Hartono, Stella R.; Malapert, Amélie; Legros, Pénélope; Bernard, Pascal; Chédin, Frédéric; Vanoosthuyse, Vincent
Abstract: R-loops, which result from the formation of stable DNA:RNA hybrids, can both threaten genome integrity and act as physiological regulators of gene expression and chromatin patterning. To characterize R-loops in fission yeast, we used the S9.6 antibody-based DRIPc-seq method to sequence the RNA strand of R-loops and obtain strand-specific R-loop maps at near nucleotide resolution. Surprisingly, preliminary DRIPc-seq experiments identified mostly RNase H-resistant but exosome-sensitive RNAs that mapped to both DNA strands and resembled RNA:RNA hybrids (dsRNAs), suggesting that dsRNAs form widely in fission yeast. We confirmed in vitro that S9.6 can immuno-precipitate dsRNAs and provide evidence that dsRNAs can interfere with its binding to R-loops. dsRNA elimination by RNase III treatment prior to DRIPc-seq allowed the genome-wide and strand-specific identification of genuine R-loops that responded in vivo to RNase H levels and displayed classical features associated with R-loop formation. We also found that most transcripts whose levels were altered by in vivo manipulation of RNase H levels did not form detectable R-loops, suggesting that prolonged manipulation of R-loop levels could indirectly alter the transcriptome. We discuss the implications of our work in the design of experimental strategies to probe R-loop functions. Graphical abstract: Image 1 Highlights: Does the affinity of the S9.6 antibody for dsRNA interfere with R-loop mapping? The S9.6 antibody immuno-precipitates G-rich dsRNA in vitro and in vivo in S. pombe . dsRNA removal allows for the mapping of two classes of RNase H-sensitive R-loops. RNaseH manipulations affect mostly the expression of genes with no R-loop detected. The affinity of S9.6 for dsRNA should be taken into account.